Study on the Use of Hybrid Coconut Coir Fiber With Polyester Resin Bqtn 157 as Composite Material Matrix - Santun I A Siallagan (International Journal of Mechanical Computational and Manufacturing Research, 2022)
The use of natural fibers as reinforcement of composites in recent years has been developing very rapidly. The purpose of this study is to investigate the mechanical properties i.e. tensile strength, impact strength and flexural strength of composites coir fiber. In the future this material can be used for vehicle accessories, ceilings and cabinet and will be able to replace the wood, eternit, bamboo and gipsun which are high price and lower water resistance.The research material made with coconut coir fiber as reinforcement and matrix resin unsaturated polyester resin BQTN 157, with 1% hardener types MEKPO (Methyl Ethyl Ketone Peroxide) and fiber treatment by 5% NaOH. Production methods are press hand lay-up and the variations of fiber volume fraction are 0, 10, 20, and 30% Testing of mechanical properties of the composite tensile strength using standard ASTM E8 M-09.J